Pengembangan Rangkaian Mesin Penetas Telur Unggas - Wire Bagye; Abdul Hafiz Bahrain; Juliyantika Ayudita .P (Teknik Elektro - Universitas Negeri Gorontalo, 2022)
To meet the demand for chicken meat in the NTB Province, the NTB Provincial Government has developed the concept of a large-scale and integrated poultry village called the Chicken Satellite program. The program facilitates poultry farmers and entrepreneurs with supporting facilities such as heating machines and egg incubators. Egg incubators held by the government apply manual settings so that every time they start hatching the user makes settings. In this study, an egg incubator was developed that can store the incubation indicator settings until it hatches into a hatching profile. the profile contains incubation mode, hatch mode, or incubation mode until hatching repeatedly. the user can go back to using those profile settings without resetting all the indicators required for eggs to hatch. By using ESP8266 as processing core. AHT10 as a sensor to measure temperature and humidity. The method used for this research is the Research and Development (RD) method. The test results show that all incubation and hatching indicators can be stored in a profile. saved profiles reach 100 different profiles.